The paradox of self-rated health following joint replacement surgery - Perneger, T; Lübbeke, A (Springer Verlag, 2018)
Purpose Self-rated health is a commonly used patient-reported outcome, but its responsiveness to is not well documented. We examined the ability of self-rated health to capture health changes attributable to a highly effective surgical intervention. <brk></brk> Methods Prospective study of patients with severe osteoarthritis of the hip (N = 990) or knee (N = 907) who underwent total hip replacement (THA) or total knee replacement (TKA). Self-rated health was assessed pre-operatively and 1 year after surgery on a scale between “excellent” and “poor,” along with other health items (other 11 items of the SF12 questionnaire) and multi-item Pain and Function scales. <brk></brk> Results On average, self-rated health was unchanged by surgery. In both THA and TKA cohorts, of 10 patients, 6 rated their health the same after surgery as before, 2 gave a higher rating, and 2 gave a lower rating. In contrast, major improvements were observed for all other SF12 items, and for the Pain and Function scales, in both cohorts of patients. Nevertheless, both before and after surgery, self-rated health was associated with the other SF12 items and with Pain and Function scores. These associations were stronger after surgery than before. <brk></brk> Conclusions Self-rated health was not responsive to major improvements in health, documented by other instruments, attributable to joint replacement surgery. However, self-rated health was even more strongly associated with concurrent assessments of more specific health problems after surgery than before. Caution is advised in interpreting changes in self-rated health following health-altering interventions.